Are sustainable drainage systems (SuDS) effective at retaining dissolved trace elements?. Issue 10 (29th April 2023) - Humphrey, Jasmine; Rowett, Chris; Tyers, Jonathan; Gregson, Mark; Comber, Sean
ABSTRACT: Sustainable drainage systems (SuDS) are increasingly deployed to mitigate against increased trace element contaminant loads associated with urban and road runoff. However, there is a lack of research on their capabilities in removing these trace elements, particularly from the dissolved phase. Water samples were taken, following various rainfall events, from three different SuDS in Devon; one wetland pond adjacent to a busy dual carriageway, a new SuDS serving a housing estate and an established SuDS draining a mixed housing/light industrial area. A total of 15 elements were studied over the course of six rain events including the first flush of runoff. Removal rates varied within and between rain events as well as between types of SuDS. Although there was a general (modest) removal of dissolved elements within any given SuDS, this was not the case for all of the elements studied. Highest observed element concentrations entering the SuDS occurred at the onset of a rain event (first flush), the intensity of which, was related to the antecedent dry period. During high flows associated with intense rainfall, the SuDS could also act as a source of trace elements associated with fine particulates (e.g. lead) owing to resuspension of fine particulate material. Mature ponds with an abundance of macrophytes help retain solids and particulate metals, however poor maintenance leading to successional growth of shrubs and trees, reduces the efficiency of metal removal. This study highlighted the importance of long-term management planning to be included within any SuDs scheme. GRAPHICAL ABSTRACT: UF0001